Successful treatment of pityriasis lichenoides et varioliformis acuta with stapokibart: a case report - Shi, Rongqiao; He, Aijuan; Ma, Zunfeng; Jiang, Mengying (Frontiers in Medicine, 2025)
Pityriasis lichenoides et varioliformis acuta (PLEVA) is a relatively rare inflammatory skin disorder encountered in clinical practice. Stapokibart is a humanized monoclonal antibody drug targeting the interleukin receptor subunit α (IL-4Rα), and is primarily used for the treatment of atopic dermatitis. Currently, owing to the rarity of PLEVA in clinical practice, there have been no reports on the use of Stapokibart in its treatment. This article presents a case in which stapokibart was used to treat a patient with acute acneiform lichenoid pityriasis, demonstrating its clinical efficacy. Following treatment with biological agents, the patient’s rash completely resolved, and their quality of life significantly improved, without any adverse reactions. This case provides a valuable reference for the clinical treatment of PLEVA.